BNPL in the Consumerism World: About the Excessive Debt Trap - Bartosz Bagniewski; Jakub Kubiczek; Zuzanna Żuchowska (Finanse i Prawo Finansowe)
The purpose of the article. This article aims to present the characteristics of BNPL and the excessive debt risk it poses within the context of widespread consumerism.